Identification of karst water inflow sources in the main shaft of Lianhuashan, Jingxiang phosphate mine, Hubei Province - Si XU; Yang YU; Peipei LIAO; Zuxu CAI; Jiaqianlin LIU; Yanmei CHEN (Shuiwen dizhi gongcheng dizhi, 2025)
Karst mining areas are characterized by pronounced heterogeneity due to extensive karst development, making them particularly susceptible to water inrush and groundwater contamination during deep extension mining. During the construction of the main shaft in Lianhuashan, the construction progress was slow because of being troubled by water inrush problems. This study identified the water-filling sources and main runoff paths of the main shaft by analyzing the hydrochemical data and isotope data before and after the pumping tests of the main shaft and surrounding hydro-holes and combining with high-precision field tracer experiments. The results show that the groundwater in drilling hole ZK02 within the Lianhuashan mining section is continuously replenished by the leakage of leachate from the southern phosphogypsum slag yard, with hydrochemical type of SO4—Mg•Ca. The hydrogen and oxygen isotopes show that atmospheric precipitation is one of the main water-filling sources of regional groundwater. After the main shaft pumping, the hydrochemical type changes from HCO3•SO4—Mg•Ca to SO4•HCO3—Mg•Ca, indicating that the drawdown funnel formed by pumping promotes the joint replenishment of the karst water of ZK01 and the leachate-polluted water of ZK02 to the main shaft. The tracer test reveals that the groundwater flow direction is from the slag yard→ZK02→ZK03→the main shaft. Regional flow is predominantly from the south, and under the structural influence of the F13 fault, leachate migrates along the Zhangjiachong syncline axis toward the F09 fault, eventually discharging through the main shaft along its dip direction. This study can provide a scientific basis for the prevention and control of karst water hazards, groundwater pollution, and the management of water resource development and utilization in the main shaft.